Modelling seafaring in Iron Age Atlantic Europe - Smith, KJ (2020)
The extent to which a European ‘Atlantic Zone’ was connected by maritime links in the Iron Age is debatable, as direct evidence is fragmentary and no accounts from contemporary inhabitants of Atlantic Europe survive. This thesis contributes to this debate by developing a new navigation model and deploying the model in the western English Channel. This thesis seeks to understand (1) whether proposed routes across the Channel would have been viable and whether other alternatives may have existed, (2) whether or not promontory forts could have been used as landmarks for navigator, and (3) how aspects of navigation – such as speed potential, landmarks, and ability to read conditions – may have affected Channel crossings. The model developed for this analysis is a fully agent-based model, in which simulated navigators follow a set of instructions without input from a human operator. A model that allows simulated ships to go off-course and potentially not reach their destinations can be used to evaluate routes in terms of risk and reliability.